Effect of French Press Brewing on the Sensory Quality of Robusta Coffee Produced in Hainan - LIU Di, LAO Fei, DONG Wenjiang, YU Xinxin (Shipin Kexue)
French press coffee with a soluble solid content (SSC) of 2% was prepared from medium roasted Hainan-grown Robusta coffee. Single factor experiments and response surface methodology were used jointly for optimization of four processing parameters based on consumer preference, and the correlation between consumer preference and sensory characteristics and flavor components was analyzed by quantitative sensory description, gas chromatography-mass spectrometry (GC-MS), and ultra performance liquid chromatography (UPLC). The results showed that the extraction yield of coffee significantly increased with the decrease in coffee grind size, the increase in powder-to-water ratio, the increase in brewing water temperature or the prolongation of brewing time (P < 0.05). Maximum liking score of (3.3 ± 1.6) (out of 6 on a 7-point hedonic scale) was obtained when the powder-to-water ratio was 1:5 (m/m), the grind size was 8, the brewing water temperature was 92 ℃, and the brewing time was 6 min. A total of 78 volatile components were detected from coffee, and 10 key aroma components such as macroketone and 3-ethyl-2,5-methylpyrazine were identified by odor activity value (OAV) analysis. Pearson correlation analysis showed that the degree of liking was positively correlated with the roundness and chocolate aroma of coffee, and negatively correlated with caffeine; 4-ethyl-2-methoxy-phenol and 2-methoxy-4-vinylphenol, with clove and phenol-like flavors; and 3-methyl-indole, with a fecal odor. This study provides a theoretical basis for exploring the flavor preference and material basis of Hainan-grown Robusta coffee.